What CARICOM is not - edited version - Gonsalves, Ralph E. (2014)
Gives a reminder that CARICOM is a community of sovereign states which has to constantly seek consensus, without the central executive mechanism legislative machinery as exists in the European Union. States that is not a supra-national entity with the authority to hold governments to account and to compel obedience.